Multi-drug resistant Mycobacterium tuberculosis in Port Harcourt, Nigeria - Kome Otokunefor; Tosanwumi V. Otokunefor; Godwin Omakwele (AOSIS, 2018)
Background: In past years, much focus has been on tackling the scourge and spread of tuberculosis worldwide. The recent emergence of multi-drug resistant (MDR) tuberculosis has, however, negatively threatened progress made so far. Nigeria ranks fourth out of the 22 high tuberculosis burden countries in the world and has the highest burden of tuberculosis in Africa. It is therefore necessary to monitor the MDR tuberculosis situation in the country. Objectives: This study set out to assess the proportions of MDR tuberculosis in patients attending six directly observed treatment short-course centres in Port Harcourt, Nigeria, from October 2015 to October 2016. Methods: Six hundred and nine participants between the ages of 18 and 75 years were enrolled in this study and comprised suspected and newly diagnosed tuberculosis cases. Sputum samples obtained from the participants were screened for the presence of Mycobacterium tuberculosis using standard culture and phenotypic biochemical techniques, and drug susceptibility testing was carried out using the 1% proportion conventional method. Results: Of the 609 participants enrolled, 30 (4.9%) were confirmed as M. tuberculosis-positive cases. A high prevalence of drug resistant tuberculosis was noted in this study (14/30, 46.7%), with 26.7% of isolates resistant to streptomycin. MDR tuberculosis, defined as being resistant to isoniazid and rifampicin, was detected in only one case (3.3%). Conclusion: This study reports a low rate of MDR tuberculosis and contributes to the sparse data on drug resistant tuberculosis in Nigeria.